2009
DOI: 10.2484/rcr.v4i2.289
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Ossicle in the Lateral Meniscus: An Unusual Variant of a Rare Entity

Abstract: Meniscal ossicles are rare entities of the knee usually involving the medial meniscus. Lateral meniscal ossicles are exceedingly rare. We present a case of a lateral meniscal ossicle found incidentally after trauma. The etiology and characteristic findings on imaging are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…Histologically, ossification demonstrates lameller and cancellous bone with fatty bone marrow surrounded by cortex, which is covered by hyaline cartilage. 1e3, 7,8 Many theories have been postulated regarding the aetiology of ossifications. They may be vestigial structures, as they are common in rodents, and domestic cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, ossification demonstrates lameller and cancellous bone with fatty bone marrow surrounded by cortex, which is covered by hyaline cartilage. 1e3, 7,8 Many theories have been postulated regarding the aetiology of ossifications. They may be vestigial structures, as they are common in rodents, and domestic cats.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,12 There is no concordance regarding treatment of meniscal ossification. However, most authors advise conservative treatment in the first instance, but arthroscopy and meniscectomy may be a choice of treatment for persistent symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…(2)(3)(4) Most cases involve the posterior horn of the medial meniscus, with fewer reports of involvement in the lateral meniscus and anterior horns. (2,3,5) Meniscal ossicles are defined as mature bone embedded within the substance of the meniscus. (5,6) Histologically, ossicles are seen as lamellar and cancellous bone with fatty bone marrow, and they are surrounded by meniscal fibrocartilage.…”
Section: Discussionmentioning
confidence: 99%
“…(2,3,5) Meniscal ossicles are defined as mature bone embedded within the substance of the meniscus. (5,6) Histologically, ossicles are seen as lamellar and cancellous bone with fatty bone marrow, and they are surrounded by meniscal fibrocartilage. (1,6,7) Several authors have reported foci of increased vascularisation, fibroblastic proliferation and even osteogenic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation